Paepalanthus conjunctus, a new species of Paepalanthus sect. Diphyomene (Eriocaulaceae) from Central Brazil - Trovó, Marcelo; Sano, Paulo Takeo (Phytotaxa, 2014)
We describe and illustrate Paepalanthus conjunctus, a new species of Paepalanthus sect. Diphyomene restricted to open humid fields in the vicinity of Brasília (DF). It can be distinguished from other species by its cespitose habit forming clumps of a few individuals, linear leaves, short reproductive axis, hairy scapes, and short corolla tubes. As the species is known from a single population growing in an area undergoing intense anthropic activity, it is considered endangered. A detailed description and illustrations, as well as comments on distribution, morphological variation, and affinities are provided.